Functional Analysis of the Microgrid Concept Applied to Case Studies of the Sundom Smart Grid - Sirviö, Katja; Kauhaniemi, Kimmo; Memon, Aushiq Ali; Laaksonen, Hannu; Kumpulainen, Lauri (Molecular Diversity Preservation International (MDPI), 2020)
The operation of microgrids is a complex task because it involves several stakeholders and controlling a large number of different active and intelligent resources or devices. Management functions, such as frequency control or islanding, are defined in the microgrid concept, but depending on the application, some functions may not be needed. In order to analyze the required functions for network operation and visualize the interactions between the actors operating a particular microgrid, a comprehensive use case analysis is needed. This paper presents the use case modelling method applied for microgrid management from an abstract or concept level to a more practical level. By utilizing case studies, the potential entities can be detected where the development or improvement of practical solutions is necessary. The use case analysis has been conducted from top-down until test use cases by real-time simulation models. Test use cases are applied to a real distribution network model, Sundom Smart Grid, with measurement data and newly developed controllers.. The functional analysis provides valuable results when studying several microgrid functions operating in parallel and affecting each other. For example, as shown in this paper, ancillary services provided by an active customer may mean that both the active power and reactive power from customer premises are controlled at the same time by different stakeholders.
Keywords: microgrids; control; use case; smart grids; fi=Sähkö- ja energiatekniikka|en=Electrical and Energy Engineering|